Answer:
y = 20
Step-by-step explanation:
-3y+12 = -48 . -12 from both sides
-3y = -60 . ÷3 on both sides
y = 20
Answer:
The answer is six
Step-by-step explanation:
12 3/5 = 63/5
2 1/10 = 21/10
63/5 divided by 21/10 is equal to 63/5 multiplied by 10/21 which is equal to 630/105 = 6 <-- answer
The algebraic expression which represents the square of the difference of s and 6 is (s - 6)²
Step-by-step explanation:
Let us represent some words by mathematics expressions
- Square a number ⇒ x²
- Square the sum of two numbers ⇒ (x + y)²
- Sum of the squares of two numbers ⇒ x² + y²
- Square of difference of two numbers (x - y)²
- The difference of square two numbers x² - y²
∵ The expression is the square of the difference of s and 6
- That means find the difference between s and 6 at first,
then square the difference
∵ The difference of s and 6 = s - 6
- Square this difference means but the difference in a bracket
and then square the bracket
∴ The square of the difference = (s - 6)²
The algebraic expression which represents the square of the difference of s and 6 is (s - 6)²
Learn more:
You can learn more about the algebraic expressions in brainly.com/question/10771256
#LearnwithBrainly
V????????????????????????????????????????????????????????????????13